SCARLETT and the Scratchy MOON - McKimmie, Chris (Crows Nest, NSW : Allen & Unwin, 2013)
"I can't sleep. The moon is moving again. It's so quiet outside ever since Holly and Sparky died." Chris McKimmie's words and pictures gently and honestly evoke the experience of loss and new life.
Keywords: Pets -- Juvenile fiction; Bereavement in children -- Juvenile fiction